UMP Foundation distributes aid, mobilises volunteers to assist flood victims - T.N., Alagesh (The New Straits Times Press (M) Bhd., 2021)
KUANTAN: To ease the burden of flood victims in Pahang, Universiti Malaysia Pahang (UMP) Foundation volunteers have been going to the ground to provide various forms of assistance.